2021
DOI: 10.1021/acs.jafc.1c04933
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Regulates Glucose and Lipid Metabolisms in Obese Mice by Restraining JNK and Activating Insulin and FGF21 Signal Pathways

Abstract: The most common complications of obesity are metabolic disorders such as nonalcoholic fatty liver disease (NAFLD), hyperglycemia, and low-grade inflammation. Sulforaphane (SFN) is a hydrolysate of glucosinolate (GLS) that is found in large quantities in cruciferous vegetables. The objective of this research was to evaluate the mechanism by which SFN relieves obesity complications in obese mice. C57BL/6J mice were fed a high-fat diet to induce obesity and treated daily with 10 mg/(kg body weight (bw)) SFN for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…SFN had been shown to improve many metabolic diseases such as obesity 27 and type 2 diabetes. 38 In our research, we found that the hepatic inflammatory factors (CCL4, IL-1β, IL-6, MCP1, TNF-α), key enzymes (CAT, GSH-PX), antioxidant indexes (MDA, SOD, T-AOC), lipid contents (LDL-C, TG) and serum biochemical parameters (FBG, GOT, GPT, LDL-C, TC, TG) of MAFLD mice were significantly improved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SFN had been shown to improve many metabolic diseases such as obesity 27 and type 2 diabetes. 38 In our research, we found that the hepatic inflammatory factors (CCL4, IL-1β, IL-6, MCP1, TNF-α), key enzymes (CAT, GSH-PX), antioxidant indexes (MDA, SOD, T-AOC), lipid contents (LDL-C, TG) and serum biochemical parameters (FBG, GOT, GPT, LDL-C, TC, TG) of MAFLD mice were significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were housed in 12 h day and night cycles in which the temperature was maintained at 20–23 °C and the humidity was maintained at 40–70%. Then, all the mice were divided into 4 groups randomly ( n = 8): control group (CN): mice fed with a maintenance diet (Xietong Shengwu Co., Nanjing, China), and given 0.4 ml PBS by gavage once a day; MAFLD group (MA): mice fed with HFD (containing 60% fat for energy, Xietong Shengwu Co., Nanjing, China), and given 0.4 mL PBS by gavage once a day; positive control group (PC): mice fed with HFD, and given 0.4 mL PPC (150 mg per kg bw) by gavage once a day; SFN group (SF): mice fed with HFD and given 0.4 mL SFN (10 mg per kg bw) 27 once a day. The nutritional composition in the maintenance and HFD are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Studies have shown that the amelioration of FGF21 resistance can correct the lipid metabolism disorders. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Studies have shown that the amelioration of FGF21 resistance can correct the lipid metabolism disorders. 17,18 Nicotinamide riboside (NR), as a form of vitamin B 3 , is a naturally occurring substance in the human diet. Inside the cells, NR boosts the concentration of nicotinamide adenine dinucleotide (NAD + ) through nicotinamide riboside kinase (NRK) and NMN adenylyltransferase (NMNAT).…”
Section: Introductionmentioning
confidence: 99%